Innovation Strategies and Digital Marketing of Clay Flower Pot SMEs in Facing Market Competition - Indri Ferdiani Suarna; Iqbal Ibnu Firdaus (Jurnal Kewirausahaan dan Multi Talenta, 2026)
Clay pot SMEs in Plered face increasingly intense market competition due to the presence of modern substitute products and shifting consumer behavior in the digital era, creating an urgent need for appropriate development strategies to ensure business sustainability. This study aims to analyze the product innovation and digital marketing strategies implemented by the SME “Puteri Aneka Murah” to strengthen its competitiveness in the local market. The research employed a descriptive qualitative method through field observations, direct interviews with the business owner, and documentation of production and marketing activities. The findings reveal that the SME conducts product innovation by developing diverse pot designs, expanding color variations, and providing customized products based on consumer demand. In marketing, the SME has begun utilizing social media platforms such as Facebook and Instagram, as well as online marketplaces, to broaden market reach. The SWOT analysis identifies strengths in product creativity and quality, alongside weaknesses such as production constraints during the rainy season and price competition. These findings imply that continuous innovation and optimization of digital marketing are essential strategies for enhancing the competitive position of clay pot SMEs.